High school students’ cognitive load on biology learning: A case study - Sunandar, Aris; Karwatisari, Rina; Rahmat, Adi; Winarno, Nanang; Hamdiyati, Yanti (Assimilation: Indonesian Journal of Biology Education, 2024)
This study aimed to analyze the cognitive load of high school students on biology learning. The method was used in this research is the survey method. The subjects of the study consisted of 179 students in grade X students consisting of 56 male students and 123 female students, 130 students in grade XI consisting of 37 male students and 93 female students, and 90 students in grade XII students consisting of 30 male students and 60 female students. The instrument in this study used a questionnaire cognitive load theory proposed by Meissner and Bogner about good learning design with a Likert scale. The results of research on high school students' cognitive load in biology revealed a medium average of 2.93, with GCL (3.29) ranking highest, followed by ICL (2.85) and ECL (2.66). The data processing results with the Kruskal Wallis test was showed that each factor has differences between ICL, ECL, and GCL. Thus, high school students still have a cognitive load when studying in class. The data processing results with the Mann U Whitney test to analyze the difference in cognitive load between male and female students was showed no significant difference between male and female students in cognitive load on biology learning.